The analysis of temperature effect on frequency dependent dielectric parameters of semifluorinated liquid crystalline biphenyl carboxylic acid - Karanlik, Gurkan; Yildiz, Alptekin; Canli, Nimet Yilmaz; Ocak, Hale; Okutan, Mustafa; Eran, Belkiz Bilgin (ELSEVIER SCIENCE BV, 2019)
In this study, the dielectric properties of the liquid crystal 4-(7,7,8,8,9,9,10,10,10-nonafluorodecyloxy)biphenyl-4'-carboxylic acid (NBCA) exhibiting a Smectic C mesophase have been analyzed. NBCA has two critical temperatures which are 194 degrees C for the crystal phase to the smectic phase transition, and 269 degrees C for the smectic phase to the isotropic phase transition. Impedance spectroscopy measurements were made at regular intervals at different temperatures which includes these transitions. By using capacitance method, the complex dielectric constants have been calculated for each temperature, and the real part of dielectric constants have been fitted to the Cole-Cole equation. In addition, ac conductivity mechanisms of the NBCA at different temperatures and different phases and also activation energies which belongs to some selected frequencies have been determined by the imaginary part of dielectric constants.
Keywords: Liquid crystal; Phase transition temperature; Impedance spectroscopy (IS); CONDUCTIVITY MECHANISM; MESOMORPHISM; MOLECULES; Physics